Organization Development: An Exploratory Literature Review - Khattak, Asmat N.; Warriach, Ali Mumtaz; Khan, Ishtiaq Alam (Annals of Human and Social Sciences, 2023)
The objective of the study is to explore the evolution of organization development (OD) and the ways in which experts have provided definitions from the beginning to the present day. This is because there is "ambiguity" for potential readers. OD is new to academics, students and practitioners. We conducted this exploratory literature review to explore the phenomena and to resolve the difficulty of "ambiguity.” The findings are "strategic revolution" and provide corporate solutions in the context of the current "polycrisis." OD suggests "rethinking", "system renewal" and “human values” and advocate for the "human factor" in decision-making. OD is a “systematic change.” The findings of the study are useful for practitioners as well as students earning masters and doctoral degrees in business administration and management sciences.